2012
DOI: 10.5194/nhess-12-671-2012
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric anomalies associated with the Haiti earthquake of 12 January 2010 observed by DEMETER satellite

Abstract: Abstract. This paper examines the ionospheric anomalies around the time of a strong earthquake (M = 7.0) which occurred in Haiti region (18.457 • N, 72.533 • W) on 12 January 2010. DEMETER satellite data have been used to study the plasma parameters variation during the Haiti earthquake. One day (11 January 2010) before the earthquake there is a significant enhancement of electron density and electron temperature near the epicenter. Decrease of electron temperature is observed few days after the earthquake. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 26 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…The dashed line circle is the earthquake preparation zone, and the solid line circles are the reduced analyzing region in the epicenter and reference point. Sarkar et al (2012) observed that N e and T e of DEME-TER concurrently increased around the epicenter 1 day before the 2010 M = 7.0 Haiti earthquake. Oyama et al (2008) reported that T e of the Hinotori satellite decreased around the epicenters within 5 days before and after the three M = 6.6 earthquakes during 1981-1982.…”
Section: Discussionmentioning
confidence: 91%
“…The dashed line circle is the earthquake preparation zone, and the solid line circles are the reduced analyzing region in the epicenter and reference point. Sarkar et al (2012) observed that N e and T e of DEME-TER concurrently increased around the epicenter 1 day before the 2010 M = 7.0 Haiti earthquake. Oyama et al (2008) reported that T e of the Hinotori satellite decreased around the epicenters within 5 days before and after the three M = 6.6 earthquakes during 1981-1982.…”
Section: Discussionmentioning
confidence: 91%
“…By applying the Kalman filter, they found an unusual increase of TEC (59% above the threshold value) just 1 d before the earthquake. By analyzing the electron density and electron temperature from the satellite DEMETER, Sarkar et al (2012) also found a significant variation 1 d before the main shock in the form of density and temperature changes. Electron density exceeded the upper bound (two standard deviations) by 20% and 9% during daytime and nighttime, respectively.…”
Section: Other Earthquakesmentioning
confidence: 95%
“…Sharma et al (2013) summarized T i and T e variations related to seismic activity during 1995-1998 over India by using SROSS (Stretched Rohini Satellite Series)-C2 satellite data in the altitude range of 430-630 km, in which significant enhancement had been detected, with 1.2-1.5 times the average normal values of T e and 1.1-1.3 times the normal T i within a 5 • window over the epicenters. Sarkar et al (2012) studied the ionospheric anomalies related to the Haiti earthquake on 12 January 2010, and their results from the DEMETER satellite showed the most important variations in N e and T e 1 day before the main shock, with T e exceeding the upper bound of ∼ 100 K and N e exceeding the upper bound by 20 and 9 % during the day-and nighttime, respectively. By using DEMETER satellite data, Zeng et al (2009) found that N e and T e decreased to a value above 20 % during local daytime near the epicenter in the 4 and 5 days prior to the Wenchuan M7.9 earthquake on 12 May 2008 in China.…”
Section: H Shen Et Al: Analysis Of the Enhanced Negative Correlamentioning
confidence: 99%
“…It was a solar-synchronous-orbit satellite, with the local time of each orbit passing the equator being the same: 10:30 in the daytime and 22:30 in the nighttime. From its records, many ionospheric perturbations related to seismic cases have been detected (Parrot et al, 2006;Sarkar et al, 2007Sarkar et al, , 2012Zhang et al, 2009Zhang et al, , 2010aZhang et al, , b, 2012aZeng et al, 2009;Pisa et al, 2011;Liu et al, 2011). Furthermore, statistical analysis of different parameters has been developed to ascertain the relationship between ionospheric perturbations and large earthquakes (Némec et al, 2009;He et al, 2010He et al, , 2011Zhang et al, 2011Zhang et al, , 2012bPisa et al, 2012;Li and Parrot, 2012).…”
Section: Introductionmentioning
confidence: 99%